ANALISIS PEMASARAN KERIPIK TEMPE DI DESA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Arinda Afif Pratiwi; Dewi Hastuti; Istanto Istanto (Universitas Wahid Hasyim, 2018)
The purpose of this study are to determine the number of marketing channels, the amount of marketing margins and marketing efficiency of tempe chips in Lerep Village, West Ungaran District Regency. The basic method of research used is descriptive method of analysis. Determination of the sample area is done purposively in Lerep Village, West Ungaran District Regency. The number of respondents as many as 15 respondents. Data analysis cost analysis and marketing margin of each marketing channel, analysis of marketing efficiency of tempe chips each channel. The results showed that there are three channels of marketing tempe chips. Channel I consists of: Producer - Final Consumer, Channel II consists of: Manufacturer - Retailer - Final Consumer and Channel III consists of : Manufacturer - Wholesaler - Retailer - Final Consumer. Total marketing margin value on channel I is Rp. 4,380, channel II is Rp. 4,500, - and channel III is Rp. 4,500. The cost incurred on channel I is Rp. 120, on channel II of Rp. 513 and on channel III is Rp. 815. The marketing of tempe chips has shown an efficient value. It can be seen from marketing efficiency value of each channel is channel I equal to 0,26%, channel II equal to 1,18%, and channel III equal to 1,87%. Channel II is an efficient channel in the marketing of tempe chips everyday. Keywords: Tempe Chips, Marketing Channels, Marketing Margin, Marketing Efficiency